Rhinosinusitis and Risk Factors - Indra Setiawan (Universitas Muhammadiyah Malang, 2023)
Rhinosinusitis is clinical syndrome characterized by ongoing or persistent symptoms of inflammation of the nasal mucosa and paranasal sinuses, namely nasal congestion, mucopurulent nasal mucus, facial pain, disturbance of smell, or cough for more than 12 weeks. The purpose of this study was to determine the risk factors affecting Chronic Rhinosinusitis. A search of studies was conducted in the main databases such as GoogleScholar, Pubmed, and Cochraine with publication time within the last 8 years and a total of 9 articles were found. Articles are selected by titles, abstracts and full text. Data is extracted by population/patient, interventions/indicators, outcome, impact and study type as well as general information from articles are also included.